Power amplifier memory polynomial predistorter for long term evolution application - Mazidi, Hossein (2015)
In Radio Frequency (RF) Front-End wireless communications systems, the power amplifier should be efficient in order to support more users and leads to decrease the costs of energy, and to extend the duration of the battery life, accordingly. Modern digital modulated signals like: Long Term Evolution (LTE) and Universal Mobile Telephone System (UMTS) exhibit difficult challenging concerns on the efficiency of the radio frequency power amplifiers and their design. Despite the spectral efficiency of these new modulated schemes, the RF PAs which are excited by the modulated signals like LTE, can experience nonlinear and unstable situation. These situations cause distortions and then result in lots of drawbacks like: power loss or heating. Therefore, some linearization techniques have been proposed to overcome the effects of non linearity. The designer can implement the digital predistortion and apply it to the input of the amplifiers for the top speed digital processors. This solution represents a significant paradigm shift for design and compensation of the nonlinear RF PAs. In this thesis, some behavioral modeling approaches of the nonlinear dynamic distortions in the wireless communication systems are investigated to model RF nonlinear PAs in order to compensate the memory effects as terms of their non linearity. A brief description of some characterization techniques will be explained. These nonlinear modeling techniques can be applied to the design of successful predistortion algorithms. The overall structure of a linearized transmitter using Memory Polynomial Digital Predistortion (MP DPD) architecture is represented to obtain both linearity and efficiency of the nonlinear PAs. The results are obtained by simulations through MATLAB. An open loop test bench is set up by using ZVE-8G+ power amplifier and Agilent equipment such as Agilent vector signal generator (VSG)EXG-D series and Agilent vector signal analyzer (VSA) PXI series in order to generate LTE down-link signal with 5 MHz bandwidth. Then, the test bench's output signal is given in arbitrary waveform format (I/Q) to the MATLAB software as the input.In conclusion, MP DPD is resulted in as improvement between 15 to 20 dB in the adjacent channel power ratio (ACPR). Therefore, the characteristics of the realized amplifiers are measured to satisfy the Error Vector Magnitude (EVM) and desired power spectral density (PSD) is plotted as requirements for Wideband Code Division Multiple Access (WiMAX) base stations and LTE down-link signal. Effect of some elements like: number of iterations, input power back-of (IBO) points, the memory effect modelling ration (MEMR) matric for different PAs with memory effects and memory-less respectively, on the performance of predistorter, are investigated.